Optimalisasi Pembelajaran Pendidikan Agama Islam melalui Pendekatan Student Centered Learning di SMP IT Al-Munadi Medan - Zahratussyafara, Nabila (IAIN PONOROGO, 2025)
This study aims to explore the student-centered learning approach to optimize Islamic religious education learning at SMP IT Al-Munadi Medan. This study was conducted to understand how the learning approach is implemented, the strategies used and the obstacles faced. Teachers act as facilitators and students are the subjects in the learning process. The use of this learning approach is in accordance with the curriculum used today. This study uses a qualitative research method with a descriptive qualitative type involving observation, interviews, and documentation to collect research data from various sources, including teachers and school administrators. The results obtained in this study prove that the implementation of learning that implies student involvement in participating and the ability to find and process information in the learning creates maximum learning, by facilitating student needs. However, teachers also face various obstacles in using this approach, such as students' lack of self-confidence and support from parents. The main conclusion of the study is that adopting a student-centered learning approach can bring significant positive changes in the world of education.